An ICT-supported intergenerational knowledge transfer framework for family firms / Sabiroh Md Sabri - Md Sabri, Sabiroh (Institute of Graduate Studies, UiTM, 2017)
In recent years, the world’s aging phenomenon has led to the increase number of retirements in organisations. When people leave their organisations, they also take with them their experience, skills and knowledge, hence leaving the organisation to suffer loss of intellectual knowledge, and certainly caused the business’s sustainability and continuity to be in danger. This phenomenon has inevitably affected family firms because their survival depends on tacit knowledge possessed by the founder as the source of its competitive advantage. Therefore, to ensure its sustainability, family firms must guarantee that their knowledge is preserved and being transferred to the successor of the business. Many researchers proposed knowledge transfer models which mostly focused on knowledge transfer methods, strategies, and processes to mitigate knowledge transfer barriers, create an optimal knowledge transfer domain for large organisations and inter-organisational knowledge transfer. However, the methods and strategies proposed were found to be ineffective for family firms, thus caused the success of knowledge transfer in family firm to be very low. This research is motivated to provide a platform for family firm to transfer their knowledge from the older generation to the younger generation with the consideration of family firm uniqueness. The qualitative approach was adopted in understanding the characteristics of family business, strategies, and mechanisms used in transferring their knowledge.